2015
DOI: 10.1017/s0022377815000100
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic gyrokinetic simulation of turbulence in torus plasmas

Abstract: Gyrokinetic simulations of electromagnetic turbulence in magnetically confined torus plasmas including tokamak and heliotron/stellarator are reviewed. Numerical simulation of turbulence in finite beta plasmas is an important task for predicting the performance of fusion reactors and a great challenge in computational science due to multiple spatio-temporal scales related to electromagnetic ion and electron dynamics. The simulation becomes further challenging in non-axisymmetric plasmas. In finite beta plasmas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 70 publications
7
67
1
Order By: Relevance
“…The same was observed in [13], where the authors reported that the trapped electron mode is not observed in the same type of calculations for the standard Large Helical Device (LHD)…”
Section: Kbm and Ideal Mhd Thresholds In W7-xsupporting
confidence: 63%
See 2 more Smart Citations
“…The same was observed in [13], where the authors reported that the trapped electron mode is not observed in the same type of calculations for the standard Large Helical Device (LHD)…”
Section: Kbm and Ideal Mhd Thresholds In W7-xsupporting
confidence: 63%
“…We remark that the radial wavenumber of the most unstable KBM in W7-X is in contrast with that of LHD [13] which is finite. The ITG mode also has the peak of the growth rate curve located around k x ρ s = 0 (Fig.3b).…”
Section: Scan In Radial Wavenumbermentioning
confidence: 71%
See 1 more Smart Citation
“…Introduction.-A finite value of normalized pressure β makes turbulence electromagnetic in magnetized plasmas, and magnetic fluctuations become important with increasing β [1][2][3][4]. The understanding of magnetic fluctuations in turbulence is an important issue in magnetic confinement and in space and astrophysics [5,6]; for instance, magnetic fluctuations have a significant impact on the normalized pressure β dependence of electromagnetic turbulent transport, which is one of the central issues in magnetized fusion plasma research, because it is linked to the fusion reaction rate and also related to the bootstrap current production that is important for steady state operation of tokamaks.…”
mentioning
confidence: 99%
“…The impact of β on confinement is not entirely clear, with different experiments showing different scalings [1][2][3]. Moreover, the effect of β on different microturbulence regimes varies, decreasing transport in ion-temperature-gradient-driven (ITG) turbulence, while increasing transport in trapped-electron-mode (TEM) turbulence [4][5][6][7]. Fast ions can further reduce ITG turbulence [9,10].…”
mentioning
confidence: 99%